Partial deletion of beta-globin gene DNA in certain patients with beta 0-thalassemia. - Orkin, S H (1979)
We have used restriction endonuclease mapping of cell DNA to investigate the structure of the beta-globin gene in beta-thalassemias. Among 17 individuals with beta +- and beta 0-thalassemia, we observed three patients of Indian origin with beta 0-thalassemia whose DNA revealed a consistent mapping abnormality. In one beta allele in each diploid cell, 0.6 kilobase of DNA was deleted from beta-specific Pst I and Bgl II restriction fragments. This deletion involved 3' beta-globin gene sequences and eliminated the EcoRI site normally present at codons 121/122, but it did not extend to the BamHI site at codons 98--100 on the 5' side of the 0.90-kilobase intervening sequence normally present in beta-globin genes. Partial beta-globin gene deletion appears, therefore, to be a primary molecular defect seen in certain patients with beta 0-thalassemia.